Religious Moderation as a Counter-Narrative of Intolerance in Schools and Universities - Aprilianto, Dwi; Aslamiyah, Siti Suwaibatul; Zahidi, Salman; Crisnasari, Nihaya Alifiya; Febbrianti, Trista (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This research is an academic effort that examines the phenomenon of intolerance and religious radicalization among high school students and college students in the cities of Lamongan and Surabaya; this study offers an actual theoretical discussion of the complex factors that shape young people's views on religious attitudes, This study aims to understand religious intolerance and radicalization among high school students and university students in Lamongan and Surabaya;  Methode of this research are quantitative and qualitative methods to understand this problem's complexity. The study begins with a quantitative survey to obtain a general picture of intolerant attitudes in both public and private schools and universities in Lamongan and Surabaya. After the quantitative survey, in-depth interviews will be conducted with high school and university students. Lamongan and Surabaya were chosen based on their well-known Islamic base and substantial variety of associations. This research shows that the experience of interacting with followers of different religions has an extraordinary impact on a culture of openness and inclusive attitudes. Some open-minded young people who befriend non-Muslims do so not because they have been introduced to inclusive teachings or views but because their daily experiences have accustomed them to interacting with friends of different faiths.